Rancang Bangun Sistem Deteksi Dini Kebakaran Berbasis Drone dengan Pengolahan Citra Digital pada Raspberry Pi - Eka Susanti; Yessy Marniati; Muhammad Hanif Fatin; Cindy Apriliya; Melna Evanti Relointri (Universitas Merdeka Malang, 2026)
Fires are a common disaster that are difficult to detect early. This study designed and built a drone-based early fire detection system using digital image processing on a Raspberry Pi. The system is equipped with a camera as the main sensor to capture images of the environment, which are then analyzed using a real-time fire color detection method. The Raspberry Pi functions as the data processing center, while the ESP32 module is used for data communication and device control. The location of the fire is identified through a GPS module, enabling accurate position monitoring. Detection results are automatically sent via the Telegram application, making it easier for users to respond to incidents. Test results show that the system is capable of detecting potential fires with fast response and high accuracy in various lighting conditions. This system is expected to be an effective solution in supporting efficient and real-time forest fire mitigation efforts